Teachers' Attitude toward ICT at Junior High Schools - Novyko Dwi Aulliah; Syafryadin Syafryadin (English Education : English Journal for Teaching and Learning, 2022)
In 21 Century, ICT is the current issue in English language teaching. After Covid 19 spreads, online learning has been carried out by the government to be carried out. However, as in many developing countries, ICT tools are provided to teachers without considering their attitudes toward ICT.  The study was focus to reveal Junior High School English teachers’ attitudes toward ICT in education. The present study used adopted questionnaire to collect the data which consist of 15 items. Both descriptive statistical method was utilized for data analysis collected from the participants. The results show that Junior high school teachers have positive attitudes toward ICT and although teachers’ attitudes toward ICT do not differ regarding gender and computer experience. It is hoped that the outcomes of this study can be used in shaping innovational practices in the Rejang Lebong Educational System. Pada abad ke-21, TIK adalah isu terkini dalam pengajaran bahasa Inggris. Setelah covid 19 merebak, pembelajaran secara daring telah dianjurakan oleh pemerintah untuk dilaksanakan. Namun, seperti di banyak negara berkembang, alat TIK disediakan tanpa mempertimbangkan sikap guru terhadap TIK. Kajian ini difokuskan untuk mengungkap sikap guru Bahasa Inggris SMP terhadap penggunaan TIK dalam pendidikan. Penelitian ini menggunakan angket yang sudah diadopsi untuk mengumpulkan data yang terdiri dari 15 item. Metode statistik deskriptif digunakan untuk analisis data yang dikumpulkan dari para peserta. Hasil penelitian menunjukkan bahwa guru sekolah menengah pertama memiliki sikap positif terhadap TIK dan sikap guru terhadap TIK tidak berbeda berdasarkan jenis kelamin dan pengalaman menggunakan komputer. Diharapkan hasil penelitian ini dapat digunakan dalam membentuk praktik inovasi dalam Sistem Pendidikan Rejang Lebong.